Classical-trajectory calculations of the electronic stopping cross-section for low-energy H and H+ projectiles by H2-molecules - Rodriguez Aguirre, Juan Manuel (2013)
A model that enables the classical-trajectory simulation of the interaction between an atomic particle and a target containing one or more electrons is devised. It makes use of the so-called Gaussian kernel approximation (GKA) and ad hoc potentials. In this way, the most relevant quantum properties of the electron can be preserved and, at the same time, still using classical mechanics to solve the response of the electronic system to the presence of a moving, heavy charge. As a first step to assessing the proposed model we calculate the electronic stopping cross section for 1keV to 20 keV Protons and Hydrogen impinging upon atomic and molecular Hydrogen targets. The results show a fairly good agreement between experiments and previous theoretical calculations over the entire bombarding energy studied in this paper